Acute Post-Exercise Myofibrillar Protein Synthesis Is Not Correlated with Resistance Training-Induced Muscle Hypertrophy in Young Men - Mitchell, Cameron J.; Churchward-Venne, Tyler A.; Parise, Gianni; Bellamy, Leeann; Baker, Steven K.; Smith, Kenneth; Atherton, Philip J.; Phillips, Stuart M. (PLOS ONE, 2014)
Muscle hypertrophy following resistance training (RT) involves activation of myofibrillar protein synthesis (MPS) to expand the myofibrillar protein pool. The degree of hypertrophy following RT is, however, highly variable and thus we sought to determine the relationship between the acute activation of MPS and RT-induced hypertrophy. We measured MPS and signalling protein activation after the first session of resistance exercise (RE) in untrained men (n = 23) and then examined the relation between MPS with magnetic resonance image determined hypertrophy. To measure MPS, young men (24±1 yr; body mass index = 26.4±0.9 kg•m2) underwent a primed constant infusion of L-[ring-13C6] phenylalanine to measure MPS at rest, and acutely following their first bout of RE prior to 16 wk of RT. Rates of MPS were increased 235±38% (P<0.001) above rest 60–180 min post-exercise and 184±28% (P = 0.037) 180–360 min post exercise. Quadriceps volume increased 7.9±1.6% (−1.9–24.7%) (P<0.001) after training. There was no correlation between changes in quadriceps muscle volume and acute rates of MPS measured over 1–3 h (r = 0.02), 3–6 h (r = 0.16) or the aggregate 1–6 h post-exercise period (r = 0.10). Hypertrophy after chronic RT was correlated (r = 0.42, P = 0.05) with phosphorylation of 4E-BP1Thr37/46 at 1 hour post RE. We conclude that acute measures of MPS following an initial exposure to RE in novices are not correlated with muscle hypertrophy following chronic RT.